Evaluation Of Iron Sucrose and Oral Iron in Management of Iron Deficiency Anaemia in Pregnancy - Rohina S, Aggarwal; Vineet V, Mishra; Navin A, Panchal; Nital H, Patel; Vrushali V, Deshchougule; Anil F, Jasani (National Journal of Community Medicine, 2012)
Objective: To compare intravenous iron sucrose with oral iron in treatment of severe iron deficiency anaemia in pregnant women presenting at Institute of Kidney Disease and Research Centre. The study was carried out in the department of Obstetrics and Gynaecology at Institute of Kidney Disease and Research Centre over a period of six months from 02-02-2010 TO 2-08-2010. Methodology: 50 cases with proven iron deficiency with Hb ≤7 gm/dl were included in the study. Total iron deficit was calculated using a standard formula. Target haemoglobin was 11 gm %. Iron sucrose was administered by intravenous infusion. Haemoglobin was repeated 1, 2, 3, and 4 weeks after the last dose of Intravenous Iron sucrose. Results: Anthropometric and biologic data for mothers in i.v. sucrose and oral iron groups was similar. Distribution of cases by economic status showed, 21 patients (42.0%) belonged to lower class, 20 patients (40%) belonged to middle class and 09 patients (18%) were of upper class.) Target haemoglobin levels were achieved in 4 weeks’ time in 19 (76%) patients in iron sucrose group as compared to 08 (32%) of patients in oral iron group. There was significant improvement in the various haematological parameters in iv sucrose group as compared to patients in oral iron group. There were no significant allergic reactions in iv sucrose group. Conclusion: This study has shown a significant improvement in anaemia in the iron sucrose group. Patients achieved the target of 11 gm %. Intravenous iron therapy is safe, convenient and more effective than oral iron therapy in pregnancy and is well tolerated.